Sensorless Sliding Mode Vector Control of Induction Motor Drives - Gouichiche Abdelmadjid; Boucherit Mohamed Seghir; Safa Ahmed; Messlem Youcef (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
In this paper we present the design of sliding mode controllers for sensorless field oriented control of induction motor. In order to improve the performance of controllers, the motor speed is controlled by sliding mode regulator with integral sliding surface. The estimated rotor speed used in speed feedback loop is calculated by an adaptive observer based on MRAS (model reference adaptive system) technique .the validity of the proposed scheme is demonstrated by experimental results.DOI: http://dx.doi.org/10.11591/ijpeds.v2i3.405